Improving The Quality Of Human Resources In The Global Era: Preparation Students Of Lingga Kencana Depok Vocational School To Face Competitive Competition - Indah Savitri, Shela; Indra Januar Rukmana; Syawaludin, Syawaludin (Journal Arbitrase : Economy, Management and Accounting, 2024)
Global competitiveness in the modern day necessitates the facilitation of high quality learning in order to provide pupils the tools they need to meet the challenges of a globalised world. The rapid pace of information flow necessitates the availability of high-caliber human resources, which naturally calls for competitive human resources, in order to analyse and filter the available data and make prompt, precise judgements. The education system as a whole depends heavily on human resources for educators and other staff members, hence these resources must be given central, first priority. Today's schools have a tremendous job to do in preparing children for a world that is changing quickly and becoming more competitive. In order to give pupils the necessary information and abilities to compete and adapt successfully in the global period, the educational system must be modified. To guarantee that students are prepared to face the demands and obstacles of a world that is always changing, innovation and a focus on the future are crucial. The factor that most influences the development of high-quality educational procedures and results is the educator. Globalisation in the modern period requires intense competition, thus educational institutions need to be able to teach well and turn out students who are the best in terms of character and aptitude to succeed in this environment. Improving instruction on digital technology, which is currently underemphasized in the curriculum, is one approach to do this. Examples of this include teaching students how to use Microsoft Word, Excel, and PowerPoint. This clause will give pupils a solid platform on which to compete in the modern digital world.